Pemenuhan Nafkah Bagi Pasangan Mental Retardation di Desa Sidoharjo Kecamatan Jambon Kabupaten Ponorogo Perspektif Keadilan Gender dalam Islam - Meilinda, Fauziyah Putri (CV. Ulil Albab Corp, 2024)
In a marriage bond produces a legal consequence, namely rights and obligations.One form of the husband's obligation to his wife is maintenance. This maintenance obligation is not determined by how much the wife and household needs, but is adjusted to the ability of the husband as the head of the household to meet his needs, as is the case with marriages carried out by couplesmental retardation, in Sidoharjo Village, Jambon District, Ponorogo Regency, which is better known as